2020
DOI: 10.3390/plants9020179
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Polyamines Modulates Winter Oilseed Rape Responses to Increasing Cold

Abstract: Cold stress is one of the most common abiotic stresses experienced by plants and is caused by low temperature extremes and variations. Polyamines (PAs) have been reported to contribute in abiotic stress defense processes in plants. The present study investigates the survival and responses of PA-treated non-acclimated (N) and acclimated (A) winter oilseed rape to increasing cold conditions. The study was conducted under controlled conditions. Seedlings were foliarly sprayed with spermidine (Spd), spermine (Spm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 71 publications
1
10
0
2
Order By: Relevance
“…The acidified ninhydrin colour reaction was used to determine proline content [ 53 , 54 ]. Each 500 g lettuce sample was ground in a prechilled mortar for 2 min, and proline with 10 mL of 3% sulphosalicylic acid (Roth) was extracted at 4 °C for 24 h. The extracts were then centrifuged at 700× g (centrifuge MPW-351 R, Poland) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidified ninhydrin colour reaction was used to determine proline content [ 53 , 54 ]. Each 500 g lettuce sample was ground in a prechilled mortar for 2 min, and proline with 10 mL of 3% sulphosalicylic acid (Roth) was extracted at 4 °C for 24 h. The extracts were then centrifuged at 700× g (centrifuge MPW-351 R, Poland) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…H + -ATPase activity in the membrane samples was assessed at 37 °C (0.5 h) by measuring the release of inorganic phosphate (Pi), which accumulates as a result of ATP hydrolysis [ 53 , 54 ]. Briefly, the plant material was gently homogenised in Tris-HCl buffer (pH 7.8).…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that abiotic stress tolerance is mainly due to PAs’ functions during signal transduction instead of PAs’ accumulation ( Pál et al., 2015 ). The exogenously applied PAs (Put, Spd and Spm) improved the proline contents, regulated the functioning of H + -ATPase of plasma membrane, and delayed the stimulation of ethylene emission under cold stress, suggesting that PAs might act as elicitors that stimulate the defensive response, which leads to compensating the adverse effect of low-temperature stress in winter oilseed rape ( Jankovska-Bortkevič et al., 2020 ). The previous findings on transgenic plants revealed that the biosynthesis of PAs was attributed to higher stress tolerance ( Kusano et al., 2008 ).…”
Section: Polyamines and Abiotic Stressesmentioning
confidence: 99%
“…Spm is specifically involved in shoot and root development, floral induction, fruit set, leaf senescence, DNA synthesis, osmolyte balance, chlorophyll protection, gene transcription, and protein translation [ 4 , 5 , 6 , 7 , 8 , 9 ]. Spm is also crucial for mounting an effective response to environmental stresses such as those caused by drought [ 10 , 11 , 12 , 13 ], heavy metals [ 14 , 15 , 16 ], excessive heat [ 17 ], low temperatures [ 18 ], and high temperatures [ 19 ].…”
Section: Introductionmentioning
confidence: 99%